Produção de biogás a partir de resíduos da avicultura: um estudo de caso no município de Tamboara - Paschoal, Fernando Augusto (2015)
This work covers the theme of biogas production from waste of poultry farming. From the biogas produced, many farms can produce electricity for domestic consumption and market the surplus energy to electric utilities. With all, talks about theimportance of this "recycling" of waste, which often are not used and end up taking up space in the properties and often environmental problems. Through this study aimed to show the main aspects regarding the necessary investment, income from the production of biogas and prospects of bioenergy for the future, as the demand for electricity consumption is growing in Brazil.